Farmer Producer Organization - Boon for Farming Community - Lade, A. H.; Ahire, R. D.; Lad, A.S. (Journal of Agricultural Extension Management, 2024)
Individual smallholders in developing countries face a number of constraints in marketing their products because of high transaction costs in the market chain, due to the gap between income and consumption. They are also unable to invest in efficiency-increasing and value-adding technologies, limiting their opportunities to increase their scale of production and effectively market their products. They also lack bargaining power. A variety of approaches have been tried, for collectivizing farmers. This paper focuses on Farmer Producer Organizations (FPOs), the objectives, structure, activities, challenges, support from the Government and presents some success stories. FPOs represent the interest of their members and have the potential to articulate their needs. However they need support to develop their capacity to serve farmers better say the authors.